1999
DOI: 10.1073/pnas.96.17.9479
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of anthranilate synthase from Sulfolobus solfataricus : Functional implications

Abstract: Anthranilate synthase catalyzes the synthesis of anthranilate from chorismate and glutamine and is feedback-inhibited by tryptophan. The enzyme of the hyperthermophile Sulfolobus solfataricus has been crystallized in the absence of physiological ligands, and its three-dimensional structure has been determined at 2.5-Å resolution with x-ray crystallography. It is a heterotetramer of anthranilate synthase (TrpE) and glutamine amidotransferase (TrpG) subunits, in which two TrpG:TrpE protomers associate mainly via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
120
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 30 publications
3
120
1
Order By: Relevance
“…4, a and b) (20). The DALI search also revealed that DJ-1 has similar topology to three proteins: the domain of catalase HPII from E. coli (17,21); the subunit of anthranilate synthase TrpG from Sulfolobus solfataricus (22,23); and the domain of GMP synthetase from E. coli (Table II) (24). All of the three proteins have flavodoxin-like Rossmannfolds and belong to the Class I glutamine amidotransferase-like superfamily (GAT superfamily) involving thiJ domains (17).…”
Section: Resultsmentioning
confidence: 99%
“…4, a and b) (20). The DALI search also revealed that DJ-1 has similar topology to three proteins: the domain of catalase HPII from E. coli (17,21); the subunit of anthranilate synthase TrpG from Sulfolobus solfataricus (22,23); and the domain of GMP synthetase from E. coli (Table II) (24). All of the three proteins have flavodoxin-like Rossmannfolds and belong to the Class I glutamine amidotransferase-like superfamily (GAT superfamily) involving thiJ domains (17).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the well characterized GATase catalytic residues cysteine, histidine, and a putative third residue, glutamate, are strongly conserved in the sequence alignment model. Among the set of sequences that belong to the identified superfamily, the small subunit of eCPS (24), GMP synthetase from E. coli (25), and anthranilate synthase from Sulfolobus solfataricus (26) have known high resolution x-ray structures with Protein Data Bank accession numbers 1jdb, 1gpm, and 1qdl, respectively. A molecular model of hGH is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The primers were used as follows. The 5 H -primer encodes a thrombin/trypsin cleavage site (LeuValProArg5GlySer, in bold letters) for later removal of the vector-designed N-terminal his 6 -tag from the purified protein. The BamHI and HindIII restriction sites in the 5 Hand 3…”
Section: Expression and Purification Of Sstrpdmentioning
confidence: 99%